Pengaruh Penggunaan Media Edpuzzle terhadap Hasil Belajar Siswa pada Pembelajaran Akidah Akhlak di MTs Al-Musaddadiyah Garut - Resti Paujiah; Acep Rahmat; Anton Anton (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2026)
The low level of student learning outcomes in the Akidah Akhlak subject at MTs Al-Musaddadiyah Garut stem from conventional instructional patterns. Over-reliance on the lecture method without varied media support makes the internalization of moral values less dynamic. Therefore, this study is presented to the effectiveness of Edpuzzle as a digital solution in transforming students' cognitive processes within the learning environment. This research employs a quantitative approach with nonequivalent control group design on 40 class IX students. Data were comprehensively gathered via observation and learning outcome tests, which was then statistically tasted through the independent sample t-test and N-Gain analysis to evaluate the effectiveness of the treatment. The analysis revealed significant findings; there is a distinct difference in student learning efficacy between the experimental classes, and the control class, with a significance value reaching 0.000. Through Edpuzzle's interactive features, the experimental class achieved learning outcome improvements in the high category, far exceeding the control class’s moderate rating. This substantiates that Edpuzzle acts as an effective catalyst, not just a technical tool, for enhancing academic achievement in Akidah Akhlak.